The Role of Temanggung State Exceptional School in Handling Children - Lina Nur Azizah; Dwi Setyawati; Dewi Sani Janatus Saada; Gilang Aldi Alamsyah; Aditia Eska Wardana (Prosiding University Research Colloquium, 2022)
This study aims to determine the role of the Temanggung State Special School in dealing with blind children. This study uses a qualitative approach with a descriptive method with data sources obtained from Class Teachers and Administrative Staff. Data collection techniques using interviews, observation, and documentation. The data obtained in the field were then analyzed with the stages of data collection, data reduction, data presentation, conclusion and verification. The results of this study are schools in dealing with blind children, especially in this learning process by providing learning that adapts to the abilities and needs of students. The strategy used in the learning process for blind children with a scientific approach, in addition to the teacher's strategy, provides learning methods in the form of lectures, demonstrations, question and answer, and roleplaying. The learning tools used in the learning process are RPP (Learning Implementation Plan), Syllabus, Prota (Annual Program), Promes (Semester Program). The form of assessment carried out by schools for blind children is diagnostic, summative, and formative assessment. Other efforts provided by the school in supporting the learning process, the school provides extracurricular and co-curricular activities. Extracurricular activities provided are in the form of scout extracurricular activities, while co-curricular activities are carried out in the form of visits to temples or outing classes.